232k views
0 votes
P(x)=x^3+2x^2-4x-8 how do you factor this polynomial function

User Avinar
by
5.8k points

1 Answer

3 votes

Steps:

So for this, I will be factoring by grouping. Firstly, factor x³ + 2x² and -4x - 8 separately. Make sure that they have the same quantity inside of the parentheses:


p(x)=x^2(x+2)-4(x+2)

Now we can rewrite it as:


p(x)=(x^2-4)(x+2)

However, we aren't finished factoring yet. The first factor, x² - 4, can be factored further using the difference of squares. The difference of squares goes by the formula here:
x^2-y^2=(x+y)(x-y) . In this case:


x^2-4=(x+2)(x-2)\\p(x)=(x+2)(x-2)(x+2)

Answer:

In short, the answer is
p(x)=(x+2)(x-2)(x+2)\ \textsf{OR}\ p(x)=(x-2)(x+2)^2

User SImon Haddad
by
6.8k points